Pengaruh Vicarious Experience Dan Social Persuasion Terhadap Self-Efficacy Petani Milenial - Mahshunah, Nur Rahmatul; Padmaningrum, Dwiningtyas; Widiyanti, Emi (Hasanuddin University, 2024)
Madiun Regency, as one of the districts that makes agriculture the foundation of regional development, empowers farmers by supporting the existence of the Madiun Millennial Farmer Community (PMM). Hopefully, this community will strengthen young people's confidence in farming. Millennial farmers' strong self-efficacy can be obtained from observing the success of other farmers. Farmers will also become more confident if they often receive praise, advice and suggestions from extension workers and other farmers. This research aims to describe and analyze the influence of vicarious experience and social persuasion on the self-efficacy of millennial farmers in Madiun Regency. The research method uses a quantitative approach, which is assisted by questionnaires, surveys, observations, interviews, documentation, and recording. Data analysis used multiple linear regression analysis using SPSS IBM 25. The results showed that vicarious experience was 48.81%, which was in the medium category, and social persuasion was 45.24%, which was in the high category. Vicarious experience and social persuasion significantly influence the self-efficacy of millennial farmers in Madiun Regency.